2016
DOI: 10.15171/jlms.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Can Antimicrobial Photodynamic Therapy (aPDT) Enhance the Endodontic Treatment?

Abstract: In order to achieve a long-lasting effect, one of the main goals in root canal treatment is to eliminate the endodontic bacteria. Conventional chemomechanical debridement is considered as the basic treatment in root canal therapy, but adjunctive techniques such as antimicrobial photodynamic therapy (aPDT) can also be helpful. The aim of this study was to evaluate reports in the scientific literature that used different photosensitizers (PSs) for bacterial reduction. The literature search was conducted using da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 59 publications
0
30
0
3
Order By: Relevance
“…The range of wavelengths for aPDT is currently 450–810 nm with a complementary application of photosensitizers. PBM effects in relation to this study may have direct application in pain modulation through the sub-ablative use of visible and near infra-red wavelengths, or may be an indirect benefit of surgical laser use at similar wavelengths within the canal and along a scatter gradient through the apex or dentinal tubules to the surrounding living tissue [ 12 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of wavelengths for aPDT is currently 450–810 nm with a complementary application of photosensitizers. PBM effects in relation to this study may have direct application in pain modulation through the sub-ablative use of visible and near infra-red wavelengths, or may be an indirect benefit of surgical laser use at similar wavelengths within the canal and along a scatter gradient through the apex or dentinal tubules to the surrounding living tissue [ 12 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have been performed both in wet and dry root canals, with promising antimicrobial results. However, overheating and melting of the root canal walls is one drawback of laser use in dry environments [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For enhanced effects a radial firing tip with optimum emission pattern of light should be used [54]. This will also result in even distribution of light and eradication of bacteria up to a depth of 1mm ensuring effective disinfection of root canal system even in cases of persistent infection where microbes like E. faecalis may penetrate up to a depth of 150 µm [55,56].…”
Section: Methods Of Usementioning
confidence: 99%
“…9 Many studies reported that these organisms can resist the antibacterial effect of calcium hydroxide. 10 Furthermore, the use of intracanal dressing forces the clinician to have multiple treatment visits and this may cause inter appointment microbial recontamination, as well as being cost and time consuming for both patients and clinicians. Laser irradiation is a new approach for disinfection of the root canal system and easier access to the hard-to-reach areas such as the tubular network.…”
Section: Comparison Of the Antimicrobial Efficacy Of Calcium Hydroxidmentioning
confidence: 99%